Numerical simulation of three dimensional two-phase flow and prediction of oil retention in an evaporator of the automotive air conditioning system. (5th May 2017) - Stevanovic, Vladimir D.; Hrnjak, Pega
Highlights: Three-dimensional model of refrigerant-oil two-phase flow is developed. R134a and 1234yf two-phase flows with PAG oil in an evaporator are simulated. Oil retention and refrigerant mass in the evaporator are numerically predicted. Numerical results are validated against measured data. Locations of oil retention inside evaporator are predicted. Abstract: This paper presents a three-dimensional model of the refrigerant-oil two phase flow developed with the aim of predicting the oil retention in evaporators of air-conditioning systems. The developed model is based on the two-fluid model approach. The governing mass, momentum and energy balance equations are written for each phase. The gas phase is the refrigerant vapor, while the liquid phase is the mixture of liquid refrigerant and oil. The balance equation for the oil mass fraction in the mixture with liquid refrigerant is included. Transfer processes at the vapor-liquid interfaces and on the flow channel walls are predicted with closure laws. The model is solved by the in-house computer code based on the SIMPLE type numerical procedure. The model is validated by comparing numerically predicted refrigerant mass and oil retention data in a brazed plate and fin evaporator, typically used in automotive applications, against measured values. Two sets of experiments performed with refrigerants R134a and R1234yf in the mixture with PAG oil are simulated. The numerical results provide a complete picture of the two-phase flow structure in the evaporator. Model predicts that oil is mainly retained in the bottom header and in smaller amounts in the top header and in parallel evaporating channels with upward refrigerant flow. The developed three-dimensional modeling and numerical approach has the advantage of being more reliable for the prediction of oil retention than existing one-dimensional models.